Controlling rectal and muscle temperatures: Can we offset diurnal variation in repeated sprint performance? - Pullinger, S. A.; Oksa, J.; Brocklehurst, E. L.; Iveson, R. P.; Newlove, A.; Burnisto, J. G (Chronobiology International, 2018)
The present study investigated whether increasing morning rectal temperatures (Trec) to resting.evening levels, or decreasing evening Trec or muscle (Tm) temperatures to morning values, would influence repeated sprint (RS) performance in a causal manner. Twelve trained males underwent five sessions [age (mean ± SD) 21.8 ± 2.6 yr, peak oxygen uptake ( peak) 60.6 ± 4.6 mL/kg min, stature 1.78 ± 0.07 m and body mass 76.0 ± 6.3 kg]. These included a control morning (M, 07:30 h) and evening (E, 17:30 h) session (5-min warm-up), and three further sessions consisting of a warm-up morning trial (ME, on a motorised treadmill) until Trec reached evening levels; and two cool-down evening trials (in 16-17°C water) until Trec (EMrec) or Tm (EMmuscle) values reached morning temperatures, respectively. All sessions included a 3 × 3-s task-specific warm-up followed by 10 × 3-s RS with 30-s recoveries performed on a non-motorised treadmill. Trec and Tm measurements were taken at the start of the protocol and following the warm-up or cool-down period. Values for Trec and Tm were higher in the evening compared to morning values (0.45°C and 0.57°C, P < 0.05). RS performance was lower in the M for distance covered (DC), average power (AP) and average velocity (AV) (9-10%, P < 0.05). Pre-cooling Trec and Tm in the evening reduced RS performance to levels observed in the morning (P < 0.05). However, an active warm-up resulted in no changes in morning RS performance. Diurnal variation in Trec and Tm is not wholly accountable for time-of-day oscillations in RS performance on a non-motorised treadmill; the exact mechanism(s) for a causal link between central temperature and human performance are still unclear and require more research